Pendekatan Saintifik dalam Pembelajaran Kelas VI SDIT Adzkia Padang - Fransisca Tassia; Nurul Hidayah (Journal on Education, 2023)
In essence, humans are destined to continue learning, so that they become useful human beings and have knowledge to be able to live, at this time education is needed in life. To get human knowledge, one must take education by means of learning, both formally and informally. In the world of education, it is inseparable from the development of ways of teaching teachers in the classroom to deliver learning material. Of course, the provision of learning material must be able to attract the attention of students, so that in the learning process in the classroom the teacher involves students to be active and creative, so that the learning process in the classroom does not feel monotonous. In presenting learning material, of course the teacher has certain approaches and methods that are matched to the learning material to be delivered, of course, the material presented in learning is expected to be understood as fully as possible by students. Such as selecting an approach to the scientific method in learning in the classroom. the scientific method can increase student enthusiasm in learning because the scientific method can provoke student activity in learning both inside and outside the classroom.